1992
DOI: 10.1111/j.1440-1746.1992.tb00958.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of the vagus nerve in the protective action of acid inhibitors on ethanol‐induced gastric mucosal damage in rats

Abstract: The role of vagus in the actions of different acid inhibitors on ethanol-induced gastric damage and mucosal blood flow (GMBF) changes was studied in anaesthetized rats, using an ex vivo stomach chamber preparation. Subdiaphragmatic bilateral vagotomy decreased the basal gastric acid secretion and GMBF; it also intensified ethanol-evoked lesions in the glandular mucosa. Misoprostol, omeprazole and cimetidine produced a similar degree of reduction in acid output. Misoprostol given subcutaneously (s.c.) (50 micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The anti-ulcer action is independent of prostaglandin synthesis but rather relies on the inhibition of gastric secretion (4). However, the importance of acid inhibition on ulcer prevention is still debatable, because reduction of gastric acidity may not decrease ulcer formation in animals (13). A recent study has demonstrated that hepa-rin, an intestinal mucosa derived polysaccharide, protects against acetic acid-induced gastric ulcer.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-ulcer action is independent of prostaglandin synthesis but rather relies on the inhibition of gastric secretion (4). However, the importance of acid inhibition on ulcer prevention is still debatable, because reduction of gastric acidity may not decrease ulcer formation in animals (13). A recent study has demonstrated that hepa-rin, an intestinal mucosa derived polysaccharide, protects against acetic acid-induced gastric ulcer.…”
Section: Discussionmentioning
confidence: 99%
“…The secretion of gastric acid has been known to be closely related to autonomic nervous tone, especially to vagal tone [9,10]. If such a relation is strong enough, the change in gastric juice pH may well induce change in autonomic nervous tone.…”
Section: Introductionmentioning
confidence: 98%
“…Evidence for central vagal gastric protective mechanisms was also demonstrated by acute ablation of the dorsal motor nucleus of the vagus (DMN) or vagotomy, which potentiated gastric lesion formation induced by EtOH 6 , 7 . In addition, an intact vagus is essential for the gastroprotective effect of prostaglandins (PG) 8 –10 . The growing literature on the central action of specific peptides to regulate gastric function through vagal pathways 11 served as a major focal point to advance our understanding of central and peripheral mechanisms underlying vagal‐dependent gastric protections 12 –14 .…”
Section: Introductionmentioning
confidence: 99%